DAMPAK MODERASI INTENSITAS RESEARCH DAN DEVELOPMENT TERHADAP PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Thio Anastasia Petronila; James Julian Surjadi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2020)
The responsibility of a company is not only to make profits, but the company is also responsible for the impact of its products and production processes on social and environmental aspects. This research aims to analyze the effect of corporate social responsibility disclosure on financial performance and analyze the relationship between corporate social responsibility and firm value with the intensity of research and development as a moderating variable. The research was conducted on companies in the consumer goods industry pharmaceutical sub-sector which were listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. Of the 10 companies there are 8 companies were sampled based on purposive sampling and from the outlier data, there are 22 observation units used in this research. The data used in this research are secondary data obtained from financial reports and annual reports. The results show that corporate social responsibility disclosure has a significant effect on a firm value which is proxied by Tobin's Q. While research and development intensity does not moderate the relationship between corporate social responsibility disclosure and firm value.